PENCEGAHAN POTENSI KERUSUHAN DI LEMBAGA PEMASYARAKATAN - Mirhandika Febytry; Arisman Arisman (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Humans are social creatures who carry out group activities and are also reliable with other humans. Therefore, humans cannot live without other people psychologically, physically, or biologically. However, with a group life that does not interact in humans, it causes incompatibility between one party and the other, resulting in all kinds of conflicts. This also applies in prisons, the emergence of conflict does not have a tremendous impact if left unchecked. The impact that occurs can be in the form of riots which of course can harm all parties, both materially and in life and safety. Therefore, in an effort to prevent potential riots in prisons, research on the causes of riots in prisons is carried out using variables in the form of cases of riots in several places that have occurred before so that they can be identified more deeply. The method used is Pareto diagram analysis, fishbone analysis, and 5W + 1H analysis.